Renal dysfunction in patients with pulmonary embolism: data from the SIRENA register - M. V. Menzorov; V. V. Filimonova; A. D. Erlikh; O. L. Barbarash; S. A. Berns; E. A. Shmidt; D. V. Duplyakov (Российский кардиологический журнал)
Aim. To assess the prevalence, severity and prognostic value of renal dysfunction (RD) in patients with pulmonary embolism (PE) of the Russian population, as well as to determine the RD significance as a marker that improves the predictive ability of current risk stratification systems.Material and methods. From April 2018 to April 2019, patients hospitalized due to PE were sequentially included in the Russian multicenter observational prospective registry SIRENA. RD was diagnosed at a glomerular filtration rate (GFR) <60 ml/ min/1,73 m2. Risk of early (hospital or 30-day) death was stratified in accordance with the current 2019 ESC Clinical Guidelines. During the study, we analyzed inpatient mortality and complication rate.Results. A total of 604 patients (men, 293 (49%); women, 311 (51%)) were in the study. RD was detected in 320 (53%) patients, while severe dysfunction — in 63 (10%) ones. In addition, 71 (12%) patients had high death risk, 364 (61%) — intermediate, 164 (27%) — low. During hospitalization, 107 (18%) patients died, including 32% from the high-risk group, 20% — moderate, and 7% — low. RD in the deceased patients was diagnosed more often, while GFR <50 ml/min/1,73 m2 reliably predicted hospital mortality (sensitivity, 67%; specificity, 72%; AUC=0,72; p<0,001). In patients with simplified Pulmonary Embolism Severity Index (sPESI) of 0 and ≥ 1, the presence of RD led to at least a 2-fold increase in mortality. Multivariate Cox regression revealed that RD is a predictor of in-hospital mortality (hazard ratio (HR), 3,41; 95% confidence interval (CI): 2,15-5,41; p<0,001), regardless of the presence of death risk reclassifies, such as high troponin (HR, 1,31; 95% CI: 0,80-2,14; p=0,28) and right ventricular dysfunction (HR, 1,23; 95% CI: 0,74-2,04; p=0,42).Conclusion. In patients with PE of the Russian population, there is a high incidence of RD, which is diagnosed in every second patient and is severe in 10% of cases. The presence of RD is associated with a significant increase in in-hospital mortality, while the risk of death increases with a decrease in GFR. The addition of RD, considered as a decrease in the estimated GFR <60 ml/min/1,73 m2, to the sPESI improves risk stratification and allows identification of patients at high risk of in-hospital death.